A high-temperature and high-pressure resistant hydrogen embrittlement resistant composite coating, a preparation method and application thereof

CN122918565APending Publication Date: 2026-10-16SHENZHEN JIANRONG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611175221.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,上述方法通常仍存在长期稳定性差、氢屏障性能不足、热不匹配或极端服务条件下导致的涂层分层等问题

Benefits of technology

[0065]本发明基于上述方案可实现如下改性机制:1)材料晶粒细化;2)梯度式应力过渡界面;3) 纳米增强的氢扩散屏障;4)自修复纳米晶相修复微裂纹;5)超声波真空致密后处理;6)超低孔隙率致密结构。所得耐高温高压抗氢脆复合涂层‌,其在80MPa氢压、105℃条件下,氢渗透率≤‌1.0×10-16mol·m/(m2·s·Pa)‌,可有效阻隔氢原子扩散,显著降低氢脆风险;涂层与基材(如不锈钢、镍基合金)的结合强度≥‌90MPa‌,确保了在热循环与机械振动下不脱落、不起层;可在‌-40~850℃‌宽温域内保持性能稳定,适用于极端冷热交替工况,通过1000次以上热震循环测试无开裂;且盐雾测试耐受时间>‌1000小时‌,无腐蚀、起泡或剥落现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918565A_ABST
    Figure CN122918565A_ABST
Patent Text Reader

Abstract

The application discloses a high-temperature and high-pressure resistant hydrogen embrittlement resistant composite coating and a preparation method and application thereof. The composite coating comprises a hydrogen trapping layer, a hydrogen blocking layer and a barrier layer arranged in sequence. The hydrogen trapping layer is a composite layer based on rare earth metal elements, alloy matrix elements and refractory metal elements. The hydrogen blocking layer is a metal-ceramic composite layer comprising a metal matrix and a nano ceramic reinforcing phase dispersed in the metal matrix. The barrier layer comprises a ceramic matrix layer, a nano reinforcing material layer and a nano metal oxide atomic deposition layer arranged in sequence. The composite coating constructed by the application can effectively inhibit hydrogen diffusion and hydrogen-induced embrittlement, and has excellent adhesion, thermal stability, corrosion resistance and good mechanical compatibility with the metal substrate. In particular, the composite coating can still maintain a long service life in a harsh hydrogen-containing environment, and is suitable for a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface engineering and material protection technology, specifically relating to a high-temperature and high-pressure resistant, hydrogen-embrittlement-resistant composite coating, its preparation method, and its application. Background Technology

[0002] Hydrogen embrittlement is a key failure mechanism for metallic materials exposed to hydrogen-rich environments, especially under high temperature and pressure. Hydrogen atoms can diffuse into the metal lattice, accumulate at defects, and induce cracking, loss of plasticity, and catastrophic failure. These problems are particularly severe in fields such as hydrogen-blended combustion, petrochemical processing, nuclear power generation, hydrogen storage and transportation, and aerospace engineering.

[0003] Existing hydrogen embrittlement prevention technologies mainly include alloy modification, surface treatment, and coating technology. However, these methods often suffer from problems such as poor long-term stability, insufficient hydrogen barrier performance, and coating delamination due to thermal mismatch or extreme service conditions. For example, traditional hydrogen embrittlement resistant materials (such as 316L stainless steel and nickel-based alloys) are prone to hydrogen permeation in high-temperature and high-pressure hydrogen environments, leading to grain boundary embrittlement and decreased mechanical properties. This risk is significantly increased, especially in hydrogen-doped burners (operating temperature ≥800℃, pressure ≥5MPa). Inorganic high-temperature coating technologies (such as single ceramic coatings) suffer from problems such as insufficient adhesion, mismatched coefficients of thermal expansion, and poor thermal shock stability. They are prone to cracking and peeling under temperature cycling conditions, failing to meet long-term service requirements. Existing composite coatings are prone to problems such as uncontrolled porosity, uneven layer thickness, residual stress accumulation, and unstable nanophase distribution during preparation, particularly limiting their performance under high temperature and high pressure.

[0004] Currently, there is a lack of products that simultaneously possess high hydrogen resistance (hydrogen permeability ≤10%). -16 mol·m / (m 2 The existing technology has failed to effectively solve the problem of synergistic corrosion caused by hydrogen embrittlement and high-temperature oxidation in hydrogen-using equipment (such as hydrogen-blended burners and petrochemical processing), resulting in shortened equipment life.

[0005] Therefore, there is an urgent need to explore a coating system that can maintain structural integrity while providing excellent hydrogen resistance and corrosion resistance under high temperature and high pressure conditions. Summary of the Invention

[0006] The main objective of this invention is to provide a high-temperature, high-pressure resistant composite coating for preventing hydrogen embrittlement and its preparation method, which can effectively suppress hydrogen diffusion and hydrogen-induced embrittlement, while also taking into account excellent adhesion, thermal stability, corrosion resistance, and mechanical compatibility with metal substrates, effectively ensuring and extending service life.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A high-temperature, high-pressure, and hydrogen-embrittlement-resistant composite coating is disclosed. This coating is a heterogeneous multiphase composite material comprising three functional layers: a hydrogen-capturing layer (bottom layer), a hydrogen-blocking layer (middle layer), and a barrier layer (outer layer), arranged sequentially. The hydrogen-capturing layer is a composite layer based on rare earth metal elements, alloy matrix elements, and refractory metal elements. The hydrogen-blocking layer is a metal-ceramic composite layer containing a metal matrix and a gradient-dispersed nano-ceramic reinforcing phase. The barrier layer comprises a ceramic matrix layer, a nano-reinforcing material layer, and a nano-metal oxide atomic deposition layer, arranged sequentially.

[0008] Furthermore, in the aforementioned high-temperature, high-pressure, and hydrogen-embrittlement-resistant composite coating, the main functions of the hydrogen-capturing layer include enhancing metallurgical adhesion, improving thermal expansion compatibility, reducing residual thermal stress, inhibiting hydrogen accumulation at the interface, and providing high-temperature and corrosion resistance. The hydrogen-barrier layer can form a gradient interface, mainly functioning to block hydrogen permeation, inhibit crack propagation, improve hardness and wear resistance, and also possess high-pressure resistance. The main functions of the barrier layer include high-temperature oxidation resistance, nanopore sealing, heat insulation, corrosion protection, enhanced fracture toughness, self-healing, and inhibition of microcracks.

[0009] In the above scheme, the hydrogen-capturing layer serves as a hydrogen diffusion inhibition and structural stabilization layer directly applied to the substrate surface. Its main function is to suppress hydrogen permeation, reduce hydrogen-induced embrittlement, improve thermal shock resistance, and enhance the metallurgical adhesion between the substrate and subsequent protective coating under high-temperature and high-pressure operating conditions. The components and their mass percentages in the hydrogen-capturing layer include: 0.01-5% rare earth metal elements, 30-75% alloy matrix elements, and 20-65% refractory metal elements.

[0010] In the above scheme, the rare earth metal element can be selected from one or more of elements and / or oxides such as cerium (Ce), lanthanum (La), ytterbium (Y), neodymium (Nd), neodymium (Pr), samarium (Sm), and neodymium (Gd). The introduced rare earth element combines with transition metals and refractory metals to promote the formation of a dense and stable composite structure, which can exhibit low hydrogen diffusion and high oxidation resistance.

[0011] In the above scheme, the alloy matrix element is selected from two or more of the following: nickel (Ni), cobalt (Co), iron (Fe), and aluminum (Al).

[0012] In the above scheme, the refractory metal element can be selected from one or more of the following high-temperature refractory metal components: chromium (Cr), molybdenum (Mo), tungsten (W), tantalum (Ta), niobium (Nb), and titanium (Ti).

[0013] In the above scheme, the rare earth metal elements introduced into the hydrogen-capturing layer can promote grain refinement and form a stable oxide dispersion phase, blocking the hydrogen migration path along the grain boundary; the alloy matrix elements have mechanical toughness, thermal expansion compatibility and high pressure crack resistance; the refractory metal elements can promote the improvement of high temperature strength, creep resistance and corrosion resistance in a hydrogen-containing environment, thereby playing a good role in high temperature and corrosion resistance.

[0014] Furthermore, the hydrogen-capturing layer, by controlling its composition and deposition conditions, forms a microstructure with a porosity of less than 3%, which is beneficial for significantly reducing hydrogen intrusion and preventing cracking; and can further serve as a transition layer to promote and improve the adhesion between the substrate and external ceramic, metal or multilayer barrier coatings.

[0015] Furthermore, the thickness of the hydrogen-trapping layer ranges from 1 to 20 μm, depending on the expected operating pressure, hydrogen concentration, and thermal exposure conditions. In high-temperature and high-pressure hydrogen environments, the hydrogen-trapping layer can promote reduced hydrogen absorption, inhibit hydrogen-induced lattice expansion and crack propagation, and maintain the structural integrity of the coated components during long-term operation.

[0016] In the above scheme, the hydrogen barrier layer is a metal-ceramic composite layer disposed on the hydrogen trapping layer. As a primary hydrogen permeation barrier and high-temperature protective layer, the hydrogen barrier layer can resist embrittlement, thermal degradation, oxidation, corrosion, and mechanical wear caused by hydrogen under high temperature and high pressure conditions. This layer consists of a dense metal-ceramic composite material structure with a gradient increasing content of nano-ceramic reinforcing phase, including a metal matrix (metal matrix phase) and nano-ceramic reinforcing phases dispersed therein at a gradient (content). The metal matrix provides ductility, toughness, and thermal expansion compatibility, while the ceramic phase provides properties such as hardness, thermal stability, resistance to hydrogen diffusion, and chemical inertness.

[0017] Furthermore, in the hydrogen barrier layer, the metal substrate material can be selected from two or more of the following: nickel (Ni), cobalt (Co), chromium (Cr), iron (Fe), molybdenum (Mo), tungsten (W), titanium (Ti), aluminum (Al), stainless steel alloys, and nickel-based superalloys.

[0018] Furthermore, the nano-ceramic reinforcing phase includes two or more of the following: nano-metal carbides, nitrides, borides, rare earth oxides, and metal hydrides.

[0019] Furthermore, the chemical composition of the nano-ceramic reinforcing phase is specifically selected from one or more of the following: alumina (Al2O3), chromium oxide (Cr2O3), zirconium oxide (ZrO2), titanium carbide (TiC), tungsten carbide (WC), silicon carbide (SiC), silicon nitride (Si3N4), boron carbide (B4C), titanium nitride (TiN), and aluminum nitride (AlN). The nano-ceramic reinforcement is dispersed throughout the metal matrix at a designed gradient concentration, which promotes the formation of a dense "brick wall" (metallic microstructure) with low porosity and tortuous hydrogen diffusion paths.

[0020] Furthermore, the nano-ceramic reinforcing phase has a nanoscale size, specifically 2-100 nm, which is beneficial for improving crack deflection, suppressing displacement movement, and enhancing mechanical strength.

[0021] Furthermore, the components and their mass percentages in the hydrogen barrier layer include: 30-90% metal matrix; 10-70% nano-ceramic reinforcing phase.

[0022] Furthermore, in addition to the metal-ceramic composite component, one or more of the following can be introduced into the hydrogen barrier layer: an interfacial binder, a diffusion inhibitor, or nano-dispersed rare earth oxide particles, to further promote and improve adhesion, thermal cycling resistance, and long-term stability.

[0023] Furthermore, the hydrogen barrier layer can provide multiple protective mechanisms, including: 1) Hydrogen barrier function: The ceramic phase reduces hydrogen permeability by blocking hydrogen diffusion channels and decreasing lattice transport rate. 2) Thermal protection function: Maintaining structural integrity at temperatures ranging from approximately 400 to 1500°C and protecting the substrate from thermal shock and localized overheating. 3) Mechanical reinforcement function: The constructed composite structure improves hardness, wear resistance, fracture toughness, and resistance to crack propagation caused by cyclic pressure loading. 4) Corrosion and oxidation resistance function: The oxide component can generate a stable passive film, which is beneficial for resisting chemical attack in hydrogen-containing, high-pressure, or reactive gas environments. 5) Stress distribution function: The metallic matrix adapts to problems such as thermal expansion mismatch between adjacent layers, which helps reduce interfacial stress and coating delamination.

[0024] Furthermore, in the hydrogen barrier layer, the content of the nano-ceramic reinforcing phase increases in a gradient from the contact surface with the hydrogen trapping layer, which can effectively improve heat resistance while maintaining interlayer adhesion.

[0025] Furthermore, the thickness of the hydrogen barrier layer is 2-100 μm.

[0026] Furthermore, the hydrogen barrier layer forms a robust intermediate barrier system that can greatly suppress hydrogen permeation and hydrogen-induced embrittlement, while maintaining high mechanical and thermal properties in harsh operating environments.

[0027] In the above scheme, the barrier layer is a high-temperature and corrosion-resistant nano-reinforced composite ceramic layer located above the intermediate hydrogen barrier layer. As the outermost environmental barrier and thermal protection layer, this layer provides excellent resistance to hydrogen permeation, oxidation, corrosion, thermal shock, erosion, and mechanical degradation under extreme high-temperature and high-pressure operating conditions.

[0028] Furthermore, the barrier layer comprises a ceramic matrix layer, a nano-reinforcing material layer, and a nano-metal oxide atomic deposition layer arranged sequentially, which effectively improves mechanical strength, fracture toughness, thermal stability, and hydrogen barrier performance. The nano-reinforcing structure forms a dense and low-porosity ceramic barrier that can resist crack initiation and propagation while maintaining structural integrity during prolonged thermal and pressure cycling.

[0029] Furthermore, the ceramic matrix layer in the barrier layer comprises one or more high-temperature ceramic materials, the main components of which include: yttrium-stabilized zirconium oxide (YSZ), zirconium oxide (ZrO2), aluminum oxide (Al2O3), chromium oxide (Cr2O3), hafnium oxide (HfO2), silicon carbide (SiC), silicon nitride (Si3N4), aluminum nitride (AlN), mullite, zirconium diboride (ZrB2), titanium diboride (TiB2), boron carbide (B4C), rare earth oxides, rare earth silicates, glass ceramic materials, etc., three or more of the following. The nano-reinforcing material is composed of one or more nanomaterials, specifically including: nano-alumina, nano-silica, nano-zirconia, carbon nanotubes (CNTs), graphene, graphene oxide, nanomaterials, nano-nitrides, nano-borides, ceramic whiskers, ceramic nanofibers, rare earth oxide nanomaterials, etc., one or more of the following.

[0030] Furthermore, the components and their mass percentages in the ceramic matrix layer and nano-reinforcing material layer of the barrier layer include: 60-99% ceramic matrix material and 1-40% nano-reinforcing material; the particle size of the nano-reinforcing material is 1-500 nm, and the formed nano-reinforcing material layer is conducive to the formation of microstructures that deflect cracks and resist hydrogen diffusion.

[0031] Furthermore, the barrier layer provides multiple protective functions, including: 1) Hydrogen permeation inhibition: The dense nano-reinforced ceramic structure creates a tortuous diffusion path, significantly reducing hydrogen permeation and the flow of hydrogen atoms through the coating. 2) High-temperature stability: In a high-pressure hydrogen environment, the ceramic matrix maintains structural and chemical stability at temperatures above approximately 800–1800°C. 3) Nano-reinforcement: The nanoscale reinforcing phase improves fracture toughness, crack bridging, crack deflection, and resistance to thermal fatigue and mechanical stress. 4) Corrosion and oxidation resistance: The ceramic matrix resists oxidation, sulfidation, chlorination, carburization, steam attack, molten salt corrosion, and chemical corrosion processes. 5) Thermal barrier and insulation: The ceramic phase reduces heat transfer to the underlying coating and substrate, thereby minimizing problems such as thermal degradation and thermal expansion mismatch. 6) Wear resistance and corrosion resistance: Under high-speed gas or particle flow conditions, the high-hardness and nano-dispersed reinforcing materials improve wear resistance, particle corrosion resistance and surface durability, and help to inhibit grain growth and microcrack formation during repeated thermal cycling, thereby improving the long-term coating reliability.

[0032] Furthermore, the porosity of the constructed barrier layer is less than 3%, preferably less than 1%; Furthermore, the thickness of the barrier layer is 2-80 μm, depending on the expected thermal exposure and hydrogen service conditions.

[0033] Furthermore, the barrier layer can form a nano-engineered ceramic shielding layer, which, together with the intermediate metal-ceramic composite layer and the bottom rare-earth alloy layer, provides comprehensive protection in high-temperature and high-pressure industrial environments, preventing hydrogen embrittlement, thermal degradation, corrosion, oxidation, and mechanical failure.

[0034] In the above scheme, the total thickness of the high temperature and high pressure resistant and hydrogen embrittlement resistant composite coating is 5-200μm.

[0035] The present invention also provides a method for preparing the above-mentioned high temperature and high pressure resistant hydrogen embrittlement-resistant composite coating. By combining laser-assisted gradient deposition, plasma-enhanced nano-spraying, artificial intelligence-assisted parameter feedback adjustment, ultrasonic-assisted densification, and vacuum nano-diffusion treatment, the resulting composite coating can take into account properties such as ultra-low hydrogen permeability, superior thermal shock resistance and crack resistance, high pressure structural stability, and adaptive pressure release behavior.

[0036] Furthermore, the high-temperature and high-pressure resistant and hydrogen embrittlement-resistant composite coating is deposited in stages to form a hierarchical structure.

[0037] Furthermore, a representative preparation method includes the following steps: 1) Substrate pretreatment The substrate to be coated with the high temperature and high pressure resistant hydrogen embrittlement composite coating is subjected to precision grinding, plasma degreasing, ultrasonic cavitation cleaning, and laser texturing in sequence. After processing, a controlled roughness structure with laser texture, micro-arched grooves, and surface roughness is formed, with Ra≤3.2μm.

[0038] 2) Preparation of hydrogen-trapping layer (bottom layer) by dual-energy simultaneous deposition Using rare earth metal materials, alloy matrix materials and refractory metal materials as the main raw materials, a dual-energy synchronous deposition process combining laser cladding and high-speed oxygen fuel spraying (HVOF) is adopted. The working mechanism includes: (1) Dual-energy synchronous deposition: laser energy and thermal spray energy act synchronously to reduce unmelted particles; increase bonding density; and form a metallurgical diffusion zone; (2) Rare earth activation mechanism: rare earth elements are refined, oxygen vacancies are reduced, and resistance to hydrogen capture is improved.

[0039] The specific process of the dual-energy synchronous process includes the following: Simultaneous activation of the laser and HVOF / HVAF spraying. The laser forms a small molten pool on the substrate surface, while the HVOF / HVAF gun sprays powder particles (rare earth metal powder, alloy matrix material powder, and refractory metal powder) into the same area. The laser and spray gun move together on the substrate surface until the required thickness is achieved. After cooling, a hydrogen-capturing layer is obtained. During dual-energy simultaneous deposition, laser energy melts part of the powder and substrate, forming strong metallurgical bonds. High-speed sprayed particles fill the voids and compact the coating, promoting the formation of a dense microstructure. The rapid heating and cooling process of the laser produces a very fine particle-amorphous composite phase, while the high-speed particle impact reduces porosity and prevents cracking. This process is repeated layer by layer to build a multilayer coating structure, which is then allowed to cool. The final result is a dense, well-adhesive coating with low porosity (<3%), which helps resist hydrogen permeation and cracking.

[0040] The process parameters for the above preparation steps include: (1) Laser cladding parameters: laser power 200-4000 watts, spot diameter 0.2-1.5 mm, scanning speed 100-1000 mm / min. (2) HVOF parameters: flame temperature 2500-3200°C, particle velocity 500-1200 m / s, powder size 5-25 micrometers, spraying distance: 150-300 mm. (3) Synchronous deposition parameters: substrate temperature 150-500°C, gradient composition control: continuous powder feeding adjustment or dual powder feeders.

[0041] The optimized parameters are as follows: laser power 1.5-3.5 kW, scanning speed 300-600 mm / min, powder feed rate 6-40 g / min, HVOF particle velocity 500-900 m / s, flame temperature 2600-2900°C, deposition rate 1-20 μm / min, substrate preheating temperature 250-450°C; and simultaneous deposition time 1-20 min.

[0042] Furthermore, after dual-energy simultaneous deposition, a vacuum diffusion annealing post-treatment is performed, with a temperature of 700-1000°C, a time of 3 min-3 h, and a vacuum degree of 10. -4 Pa-10 -2 Pa.

[0043] Furthermore, in the dual-energy synchronous deposition process, real-time sensors are used to monitor parameters such as plasma temperature, particle velocity, deposition thickness, porosity, and residual stress, and the deposition parameters are adjusted and optimized accordingly, including plasma current, gas flow, deposition rate, and matrix temperature.

[0044] 3) Gradient deposition of hydrogen barrier layer (intermediate layer) metal-ceramic composite layer By combining gradient deposition technology based on cold spray (CS) and plasma-enhanced magnetron sputtering (PEMS) processes, the concentration of ceramic components gradually increases along the thickness direction, resulting in a gradient composite structure with a metal-rich lower layer, a balanced middle layer (with comparable metal matrix and ceramic components), and a ceramic-rich upper layer. This effectively reduces problems such as thermal mismatch, significantly reduces interface cracking, and improves hydrogen diffusion tortuosity.

[0045] Furthermore, the specific deposition steps of the hydrogen barrier layer include the following: (1) cleaning the surface of the substrate containing the hydrogen trapping layer; (2) firstly, using cold spray technology to deposit a metal substrate layer mainly composed of metal matrix material, and high-speed solid particles impact to generate a dense coating; (3) then using plasma-enhanced magnetron sputtering process to sequentially deposit a metal-ceramic intermediate balance layer with increasing nano-ceramic reinforcing phase content and a ceramic substrate upper layer mainly composed of ceramic material; plasma-assisted increase of ion bombardment and density and reduction of defects; thus obtaining a hydrogen barrier layer with a gradient structure.

[0046] Furthermore, the thickness of the hydrogen barrier layer is 2-100 micrometers.

[0047] In the above scheme, the deposition parameters used in the cold spray technology are as follows: process gas N2 or He, gas pressure 2-5MPa, gas temperature: 200-900°C, particle (powder raw material) velocity 500-1200m / s, powder (metal raw material) size 5-50 micrometers, and spray distance 10-50mm.

[0048] In the above scheme, the parameters used in the plasma-enhanced magnetron sputtering process are as follows: chamber pressure 0.2-10 Pa; sputtering gas argon, flow rate 0.02-0.2 L / min; power 0.5-10 KW; plasma intensity 10. 9 -10 11 cm -3 Deposition rate: 0.1-30 μm / min.

[0049] Furthermore, the optimized parameters are as follows: plasma current 350-650 A, chamber pressure 0.5-5 Pa, deposition temperature 450-850°C, ceramic material feed ratio 40-85%, and cooling rate 5-25°C / min.

[0050] Furthermore, in the metal substrate layer, the content of the nano-ceramic reinforcing phase is 10-20%; in the metal-ceramic intermediate balance layer, the content of the nano-ceramic reinforcing phase is 20-50% (and greater than the content of the nano-ceramic reinforcing phase in the metal substrate layer); and in the ceramic substrate upper layer, the content of the nano-ceramic reinforcing phase is 30-60% (and greater than the content of the nano-ceramic reinforcing phase in the intermediate balance layer).

[0051] The above-mentioned gradient coating construction process based on CS-PEMS can achieve a dense microstructure with strong adhesion (>30-120 MPa) and porosity (<1%), which can significantly improve resistance to thermal cycling and mechanical loads and significantly reduce hydrogen permeability.

[0052] 4) Multi-field synergistic deposition preparation of a nano-reinforced composite ceramic layer for the barrier layer (outer layer) Using ceramic matrix precursor materials and nano-reinforcing materials as the main raw materials, composite ceramics were deposited sequentially by suspension plasma spraying (SPS) and nano-reinforcing phases were deposited by nano-aerosol deposition (NAD). Then, metal-organic precursors of metal oxides were used as raw materials for densification by atomic layer deposition (ALD) technology to obtain the barrier layer.

[0053] The nano-reinforcement mechanism mainly employs nanoparticles to fill micropores, create tortuous hydrogen diffusion channels, and improve fracture toughness.

[0054] Further, the specific steps for barrier layer deposition and preparation are as follows: 1. First, clean the surface of the substrate with the hydrogen replenishment layer and hydrogen barrier layer already in place; 2. Deposit the base coating using SPS: Add a 5-30 wt% ceramic matrix material suspension to a plasma jetter and perform suspension plasma spraying to form a ceramic-based SPS coating (constructing a main coating with a fine microstructure); 3. Using nano-reinforcing material powder as raw material, deposit the aforementioned nano-reinforcing phase material using nano-aerosol deposition (NAD): Deposit a thin layer of nano-reinforcing material on the surface of the obtained ceramic-based SPS coating to form nano-aerogel. The nano-aerogel helps reduce porosity, thermal conductivity, or hydrogen diffusion, depending on the application requirements. 4. Use ALD sealing and densification: Using metal-organic precursors of metal oxides as raw materials, use ALD to deposit an ultrathin, conformal nano-metal oxide atomic deposition layer on the coating surface and within the pores, which can seal micropores and improve barrier performance. 5. Final curing or heat treatment: If necessary, dry or heat treat the coating to stabilize the structure.

[0055] Furthermore, if necessary, multi-layered composite structures can be constructed prior to final curing or heat treatment: repeating the SPS, aerosol deposition, and ALD sealing steps to achieve the desired thickness and performance.

[0056] Combining the above-mentioned methods, such as SPS-deposited ceramic substrate, nano-aerosol-filled area, and ALD sealing surface, is beneficial to constructing a highly uniform, low-porosity composite coating system, which can effectively enhance resistance to hydrogen permeation, corrosion, and cracking.

[0057] Furthermore, the solid content of the ceramic matrix material in the suspension is 5-30%, with the remainder being water; the raw material used in the nano-aerosol deposition (NAD) process is the aforementioned nano-reinforcing phase powder particles (such as nano-oxides, carbides, and other solid powders). The raw material used in the atomic layer deposition (ALD) process is the metal-organic precursor corresponding to nano-metal oxides; specifically, trimethylaluminum (TMA) can be selected, which forms a dense nano-oxide coating (such as nano-alumina) after deposition.

[0058] In the above scheme, the process parameters for the suspended plasma spraying (SPS) step include: plasma power: 20-80KW, plasma gas Ar / He, substrate temperature 100-600 ℃, plasma temperature 8000-19500℃; the process parameters for nano-aerosol deposition (NAD) include: carrier gas He flow rate 10-30 L / min, aerogel chamber pressure 20-70 KPa, deposition chamber vacuum degree 10-200Pa, particle impact velocity 200-600 m / s; the process parameters for the atomic layer deposition (ALD) step include: pressure 0.1-10 Torr, temperature 80-300℃, growth rate 0.05-0.15nm / cycle, number of cycles 100-5000, and layer thickness 10-500nm.

[0059] The optimized parameters are as follows: SPS temperature 9000-15000°C plasma nucleus, nano-suspension concentration 5-20% by weight; NAD aerosol chamber pressure 50-70 kPa, deposition chamber vacuum 120-200 Pa, particle impact velocity 400-600 m / s; ALD cycle number 100-1000, carrier gas flow rate 20-60 L / min, and layer cooling rate 2-10°C / min.

[0060] Furthermore, during the barrier layer deposition process, the deposition thickness of each functional layer is as follows: SPS layer (ceramic substrate layer) 1-70μm, nano aerosol layer (nano reinforcing material layer) 0.5-20μm, ALD layer (nano metal oxide atomic deposition layer) 10-500nm, and the total thickness of the barrier layer is 2-80μm.

[0061] The barrier layer is prepared by combining high deposition rate (SPS), room temperature super-density aerosol surface formation (NAD), and atomic level pore sealing (ALD) processes. First, a porosity structure of 1-10% is obtained through SPS deposition. Then, a porosity of <1% is obtained through NAD deposition. After ALD densification, the porosity of the barrier layer is <0.1%, which promotes ultra-high density and excellent hydrogen barrier performance.

[0062] 5) Dense treatment of multilayer composite materials by ultrasonic vacuum isostatic pressing or laser remelting The composite coating obtained in step 4) is further subjected to ultrasonic vacuum hot isostatic pressing densification or laser remelting to form a denser composite coating structure.

[0063] Furthermore, the ultrasonic vacuum hot isostatic pressing densification process utilizes ultrasonic vibration to collapse nanopores, redistribute residual stress, and improve interlayer diffusion. The vacuum hot isostatic pressing environment inhibits oxidation and enhances compactness. The laser remelting process uses surface tension to drive recombination, eliminating porosity, incomplete fusion, and microcracks. These processes promote the acquisition of a composite coating with a final porosity of <0.1%.

[0064] Furthermore, the ultrasonic vacuum thermo-isostatic pressing parameters include: ultrasonic frequency 15-40 kHz, ultrasonic power 1-5 KW, and vacuum degree 10. -1 -10 -3 Pa, isostatic pressure 60-120Pa, working temperature 500-1150°C, heat and pressure holding time 0.5-4 hours; laser remelting parameters: laser power 150-800W, laser pulse energy 3-10 J, pulse width 5-30 ns, scanning speed 400-1500mm / s, spot diameter 50-3000 micrometers, overlap ratio 40-60%.

[0065] Based on the above scheme, this invention achieves the following modification mechanisms: 1) material grain refinement; 2) gradient stress transition interface; 3) nano-reinforced hydrogen diffusion barrier; 4) self-healing nanocrystalline phase repair of microcracks; 5) ultrasonic vacuum densification post-treatment; 6) ultra-low porosity dense structure. The resulting high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating exhibits a hydrogen permeability ≤ 1.0 × 10⁻⁶ under 80 MPa hydrogen pressure and 105 °C conditions. -16 mol·m / (m 2 With a strength of ·s·Pa, it can effectively block the diffusion of hydrogen atoms and significantly reduce the risk of hydrogen embrittlement; the bonding strength between the coating and the substrate (such as stainless steel and nickel-based alloys) is ≥90MPa, ensuring that it will not peel off or delaminate under thermal cycling and mechanical vibration; it can maintain stable performance in a wide temperature range of -40~850℃, and is suitable for extreme hot and cold alternating working conditions. It has passed more than 1000 thermal shock cycles without cracking; and it has a salt spray test tolerance time of >1000 hours without corrosion, blistering or peeling.

[0066] Compared with the prior art, the beneficial effects of the present invention include: 1) The composite coating described in this invention has excellent hydrogen permeation and hydrogen embrittlement inhibition functions; the hydrogen permeability is reduced by 50-100 times compared with traditional materials, and it remains stable under 80MPa hydrogen pressure, avoiding cracks caused by hydrogen embrittlement; it has excellent high temperature resistance and a wide temperature adaptability range, exhibiting high thermal stability at temperatures exceeding 850°C, making it suitable for extreme hot and cold alternating conditions, and showing no cracking after more than 1000 thermal shock cycles; it also has excellent high temperature and high pressure resistance, maintaining high temperature and high pressure resistance and good structural integrity at temperatures exceeding 850°C and pressures exceeding 130 MPa. 2) The composite coating described in this invention has excellent adhesion, with strong adhesion to metal substrates, reaching an adhesion strength of over 80MPa, ensuring that it does not peel off or delaminate under thermal cycling and mechanical vibration, thus reducing the risk of delamination. 3) The composite coating described in this invention has a long service life in harsh hydrogen-containing environments; it is suitable for key components such as nozzles and pipelines of pulverized coal hydrogen-blended burners, as well as high-temperature and high-pressure equipment such as petrochemical equipment, high-temperature hydrogen reactors, nuclear reactor components, hydrogen energy systems and high-pressure vessels, aerospace and energy conversion systems, etc. Attached Figure Description

[0067] ‌ Figure 1 This is a partial cut-out diagram of the composite coating structure according to an embodiment of the present invention. In the figure, 1-substrate, 2-hydrogen trapping layer, 3-hydrogen barrier layer, 4-barrier layer.

[0068] Figure 2 This is a schematic diagram of the coating preparation process according to an embodiment of the present invention.

[0069] Figure 3 This is a schematic diagram of the dual-energy simultaneous deposition process that combines laser cladding with high-speed oxygen fuel spraying (HVOF) used in this invention. Detailed Implementation

[0070] The applicant will now provide a more detailed description of the present invention with reference to specific embodiments, so that those skilled in the art can more clearly understand the present invention. However, the following content should not be construed as limiting the scope of protection claimed in the claims of the present invention. Example

[0071] A high-temperature, high-pressure resistant, hydrogen embrittlement-resistant composite coating (see schematic diagram) Figure 1 The preparation process flow diagram is shown below. Figure 2 and Figure 3 Its preparation method includes the following steps: 1) Pre-treat the 18mm thick alloy steel X52 metal substrate. The specific steps are as follows: a) Precision polishing and grinding: Precision grinding and polishing are performed sequentially using 120-mesh and 320-mesh abrasives until the target surface roughness Ra=2.5 micrometers.

[0072] b) Plasma degreasing: gas Ar + O2, O2 content 20 vol%, chamber pressure 45 Pa, voltage 450 V, processing time 18 minutes; effectively removes organic pollutants and activates metal surfaces.

[0073] c) Laser surface texturing: A pulsed fiber laser is used to etch microgrooves and honeycomb-like microstructures on the substrate surface to facilitate coating adhesion; the specific processing parameters are controlled as follows: laser wavelength 1064 nm, pulse frequency 60 kHz, power 850 W, groove spacing 120 μm, and groove depth 40 μm; the above processing technology can significantly improve interlayer adhesion and stress transfer capability; the surface roughness is controlled to Ra≤3.2 μm.

[0074] 2) Hydrogen trapping layer deposition, using a dual-energy simultaneous deposition process (see process flow diagram). Figure 3 The hydrogen-trapping layer is designed with the following composition: Ni 48%, Co 18%, Al 8%, Cr 22%, Y₂O₃ 2%, CeO₂ 2%. The specific deposition steps are as follows: A hydrogen-capturing layer with a thickness of 5-15 micrometers was deposited on a pretreated substrate using a dual-energy simultaneous deposition method of laser cladding and high-speed oxygen fuel spraying (HVOF). The deposition process parameters were as follows: laser power 3.2 kW, scanning speed 600 mm / min, powder feed rate 28 g / min, HVOF particle velocity 600 m / s, flame temperature 2600°C, deposition rate 10 μm / min, simultaneous deposition time 2 min, and substrate preheating temperature 360°C.

[0075] Then, vacuum diffusion annealing was performed at a temperature of 920°C for 2 hours, with a vacuum degree of 10. -3 Pa yields a hydrogen-capturing layer with a thickness of 3 μm.

[0076] 3) Hydrogen barrier layer deposition: The hydrogen barrier layer is designed with a gradient of ceramic phase content along its thickness direction, specifically as follows: the metal substrate layer (the side in contact with the hydrogen trapping layer, with a thickness of 0.5-15 μm, adopts a metal-rich structure, and the components and their mass percentages are: 85% nickel-chromium alloy and 15% TiN-Al2O3 ceramic phase; the metal-ceramic intermediate balance layer, with the components and their mass percentages being: 55% nickel-chromium alloy and 45% ceramic phase, and the thickness of the intermediate layer is 0.5-10 μm; the ceramic substrate upper layer (with a thickness of 1-10 μm), with the components and their mass percentages being 20% ​​nickel-chromium alloy and 80% ceramic phase.

[0077] First, a metal-based coating is deposited using cold spray technology. The deposition parameters are as follows: process gas N2, gas pressure 3MPa, gas temperature 600°C, particle velocity 700m / s, average raw material powder size 20 micrometers, and spray distance 30mm.

[0078] Then, plasma-enhanced magnetron sputtering was used to deposit an intermediate equilibration layer and an upper ceramic-based coating. The deposition parameters were as follows: plasma current 540 A, chamber pressure 2.5 Pa, deposition temperature 720°C, and argon flow rate 42 L / min. The final porosity was 0.25%.

[0079] The average thickness of the resulting hydrogen barrier layer is 16 micrometers.

[0080] Barrier layer deposition: Using the aforementioned deposition process, the components and their mass percentages in the ceramic matrix layer and nano-reinforcing material layer of the designed barrier layer are as follows: nano ZrO2 40%, nano Al2O3 15%, YSZ 10%, 20% SiC, La2O3 2%; carbon nanotubes 8%, h-BN 5%; A combined nano-sealing technique of suspended plasma spraying (SPS), nano-aerosol deposition (NAD), and atomic layer deposition (ALD) was employed for deposition. The SPS process parameters were: plasma power 50 kW, plasma temperature 12800 °C, spray distance 95 mm, and solid content concentration of the suspension (ceramic component suspension) 12 wt%. The resulting ceramic substrate layer thickness was 18 μm. The NAD process parameters were: nano-powder deposition, aerosol chamber pressure 60 kPa, deposition chamber vacuum 180 Pa, and particle impact velocity 550 m / s. m / s (the thickness of the obtained nano-reinforced material layer is 1.82 μm); ALD process parameters are: trimethylaluminum as raw material for deposition (forming a dense nano-Al2O3 layer after deposition, with an atomic deposition layer thickness of about 80 nm), ALD deposition cycle number of 650, single cycle growth rate of about 0.12 nm, chamber temperature of 220°C, pulse interval of 2.5 seconds; carrier gas flow rate of 38 L / min, cooling rate of 6°C / min; finally achieving effective sealing of nanopores below 20 nm.

[0081] The resulting barrier layer has a porosity of <0.1% and a total thickness of 20 micrometers.

[0082] 5) Dense multi-layer composite structure: The multilayer composite formed above was further densified using ultrasonic vacuum hot isostatic pressing (UHMPa). The process parameters used were as follows: isostatic pressing pressure 160 MPa, temperature 1050°C, ultrasonic frequency 28 kHz, ultrasonic power 3 kW, and vacuum degree 10. -2 Pa, heat preservation and pressure holding time 3 hours.

[0083] The dense composite coating material obtained by the above deposition technique has an overall porosity of <0.1%; it has no visible cracks and exhibits strong adhesion to the substrate; other performance test results are as follows: Hydrogen permeability test: The composite coating obtained in this embodiment was tested using the electrochemical hydrogen permeation method under conditions of 80 MPa hydrogen pressure and 105°C. The hydrogen permeability obtained was ≤ 1.0 × 10⁻⁶. -16 mol·m / (m 2 The ·s·Pa) can effectively block the diffusion of hydrogen atoms and significantly reduce the risk of hydrogen embrittlement. In addition, it can effectively reduce hydrogen permeability by 99.8%, oxidation depth <0.1 micrometer, and thermal fatigue resistance for 3200 cycles.

[0084] Adhesion test: The adhesion of the obtained composite coating was tested using a hydraulic pull-out tester. The results showed that the bonding strength between the coating and the substrate was ≥90MPa, ensuring that the coating would not peel off or delaminate under thermal cycling and mechanical vibration.

[0085] Durability and corrosion resistance testing: Tested in a salt spray chamber, the salt spray test withstand time is >1000 hours, with no corrosion, blistering, or peeling. No thermal stress cracks are observed after more than 1500 thermal shock cycles.

[0086] Example

[0087] A high-temperature, high-pressure resistant, and hydrogen-embrittlement-resistant composite coating is prepared by the following steps: 1) The metal substrate made of nickel-based alloy 625 is pretreated, and the specific steps are as follows: a) Precision polishing and grinding: Precision polishing is performed sequentially using 150-mesh and 350-mesh abrasives until the target surface roughness Ra=2.0 micrometers.

[0088] b) Plasma degreasing: gas Ar + O2 (O2 content 20%), chamber pressure 35 Pa, voltage 400 V, processing time 25 minutes; effectively removes organic pollutants and activates metal surfaces.

[0089] c) Laser surface texturing: A pulsed fiber laser is used to etch microgrooves and honeycomb-like microstructures on the substrate surface to facilitate coating adhesion; the specific processing parameters are controlled as follows: laser wavelength 1064 nm, pulse frequency 60 kHz, power 850 W, groove spacing 120 μm, and groove depth 40 μm; the above processing technology can significantly improve interlayer adhesion and stress transfer capability; the surface roughness is controlled to Ra≤3.2 μm.

[0090] 2) Hydrogen trapping layer deposition: A dual-energy simultaneous deposition process was employed. The hydrogen trapping layer was designed with a composition of 20% Ni + 13% Co + 30% Cr + 16% Al + 1% Y + 20% Nd₂O₃ nano-dispersion. The specific deposition steps are as follows: The material was prepared using a dual-energy simultaneous deposition technique of laser cladding and high-speed oxygen fuel spraying (HVOF). The laser power was 2.6 kW, the scanning speed was 500 mm / min, the powder supply rate was 22 g / min, the scanning spacing was 0.7 mm, and the shielding gas was an Ar-He mixture. The HVOF particle velocity was 700 m / s, the flame temperature was 2800°C, the deposition rate was 20 μm / min, and the simultaneous deposition time was 1 min. Then, vacuum diffusion annealing was performed at a temperature of 850°C for 2.5 hours and a vacuum degree of 10. -4 Pa yields a hydrogen-capturing layer with a thickness of 5 micrometers.

[0091] 3) Hydrogen barrier layer deposition: The hydrogen barrier layer is designed with a gradient of ceramic phase content along its thickness direction. Specifically, the components and their mass percentages in the metal substrate layer (the side in contact with the hydrogen trapping layer, with a thickness of 2-20 μm) are: NiCrCo 30%, MoTi 25%, CrN 30%, TiN 15%; the metal-ceramic intermediate equilibrium layer has the following components and their mass percentages: Al2O3 30%, Fe2O3 15%, SiC 30%, WC 15%, NiCr 10%, with a thickness of 2-25 μm; and the ceramic substrate upper layer (with a thickness of 2-10 μm) has the following components and their mass percentages: 40% Cr2O3, 40% ZrO2, 20% AlN.

[0092] A metal-based coating was deposited using cold spray technology. The deposition parameters were as follows: process gas N2 or He, gas pressure 2 MPa, gas temperature 500°C, particle velocity 800 m / s, powder size 15 micrometers, and spray distance 25 mm.

[0093] A middle equilibration layer and an upper ceramic-based coating were then deposited using plasma-enhanced magnetron sputtering. The deposition parameters were as follows: plasma current 500 A, chamber pressure 2.0 Pa, deposition temperature 650°C, argon flow rate 35 L / min, and nitrogen flow rate 20 L / min. The final porosity of the hydrogen barrier layer was 0.15%.

[0094] The average thickness of the resulting hydrogen barrier layer is 26 micrometers.

[0095] 4) Barrier layer deposition: The multi-field synergistic deposition coupled intelligent control process designed the following components and their mass percentages in the ceramic matrix layer and nano-reinforcing material layer of the barrier layer: zirconium oxide ZrO2 (10%), chromium oxide Cr2O3 (15%), silicon nitride Si3N4 (10%), zirconium boride ZrB2 (35%), nano YSZ (5%), graphene (10%), and nano h-BN (15%).

[0096] Nanomaterials were deposited using suspended plasma spraying (SPS), nanoaerosol deposition (NAD), and atomic layer deposition (ALD) processes. The SPS feed rate was 22 mL / min, the plasma gas flow rate was 54 L / min, the nanomaterial particle size was 20-40 nm, and the spray angle was 90°. Other parameters were the same as in Example 1.

[0097] The resulting barrier layer has a thickness of 15 micrometers.

[0098] 5) Multi-layer composite layer densification treatment: Laser remelting impact densification is adopted: Laser shot peening improves residual compressive stress and hydrogen permeation resistance, preventing hydrogen permeation. Specific process parameters include: laser pulse energy 8 J, pulse width 20 ns, spot diameter 2 mm, and overlap ratio of 50%.

[0099] The porosity of the final dense composite coating material is <0.1%; other performance test results are as follows: Hydrogen permeability test: The hydrogen permeability was tested using the electrochemical hydrogen permeation method under conditions of 80 MPa hydrogen pressure and 15℃. The hydrogen permeability was ≤ 1.21 × 10⁻⁶. -17 mol·m / (m 2 The result of ·s·Pa) indicates that the composite coating obtained in this embodiment effectively blocks the diffusion of hydrogen atoms and significantly reduces the risk of hydrogen embrittlement.

[0100] Adhesion test: The adhesion of the obtained composite coating was tested using a hydraulic pull-out tester. The results showed that the bonding strength between the coating and the substrate was ≥ 95MPa, ensuring that the coating would not peel off or delaminate under thermal cycling and mechanical vibration.

[0101] High temperature and thermal shock resistance test: The composite coating can maintain stable performance in a wide temperature range of -40~850℃ after being subjected to heating and cooling cycle test in a high temperature furnace. It has passed more than 1,000 thermal shock cycles without cracking, indicating that the coating is suitable for extreme hot and cold alternating conditions.

[0102] Interface delamination test: Conditions: 850°C; 55 MPa hydrogen gas; 800 hours of exposure. Results: No interface delamination; hydrogen diffusion coefficient reduced by 98%; fatigue life increased by 5.2 times.

[0103] Application Example 1 The composite coating described in Example 1 was applied to a high-pressure hydrogen environment for testing on a high-pressure hydrogen pipeline section. Specifically, the coated component was exposed to a hydrogen atmosphere at a pressure of 15 MPa and a temperature of 850°C for 500 hours.

[0104] No delamination, cracking, or performance degradation of the coating was observed after the test was completed.

[0105] Application Example 2 The composite coating described in this invention was applied to the nozzle of a hydrogen-doped burner to evaluate its comprehensive performance under extreme multi-physics coupled environments. The specific coating substrate and coating parameters are as follows: The burner substrate is made of 304 stainless steel with a pre-treated Ra=2.8μm.

[0106] The composite coating system described in Example 2 was tested in a simulated pulverized coal hydrogen-blended combustion system with a hydrogen blending ratio of 10%, a hydrogen partial pressure of 0.5-10 MPa, and a flame zone temperature gradient of 800-1600℃.

[0107] Test results show that the coating showed no cracking, dust accumulation, or corrosion after 1000 thermal shock cycles. The measured hydrogen permeability was 4.2 × 10⁻⁶. -17 mol·m / (m 2 The concentration of ·s·Pa indicates that the coating has good high-temperature resistance, corrosion resistance, and hydrogen embrittlement resistance.

[0108] Comparative Example 1 Uncoated stainless steel alloy samples showed obvious cracks after being subjected to 300°C and 80MPa hydrogen pressure for 300 hours.

[0109] The sample coated with the composite coating of the present invention did not show any cracks after 1000 hours at 900°C and 80MPa hydrogen pressure, and the adhesion was as high as 98.2MPa.

[0110] Comparative Example 2 A hydrogen embrittlement resistant composite coating has a composition design that is largely the same as that of Example 1, except that the functional layer is prepared using only a plasma-enhanced magnetron sputtering process (the specific process parameters are the same as those in Example 1).

[0111] The brittle composite coating obtained in this comparative example was subjected to performance tests including coating porosity, hydrogen permeability reduction rate, thermal shock cycling, adhesion, oxidation depth, pyrolysis density, and interfacial delamination. The test conditions were: hydrogen pressure: 120 MPa, temperature: 1100℃, and exposure time: 800 hours. The results are shown in Table 1.

[0112] Comparative Example 3 A hydrogen embrittlement resistant composite coating has a composition design and preparation process that are largely the same as those in Example 1, except that the densification post-treatment described in step 5) is not performed in the preparation method.

[0113] The brittle composite coatings obtained in Example 1 and Comparative Examples 1-3 were subjected to performance tests including coating porosity, hydrogen permeability reduction rate, thermal shock cycling, adhesion, oxidation depth, pyrolysis density, and interfacial delamination. The test conditions were a hydrogen pressure of 120 MPa, a temperature of 1100 °C, and an exposure time of 800 hours. The specific test results are shown in Table 1.

[0114] Table 1. Performance test results of the hydrogen embrittlement resistant composite coatings obtained in the examples and comparative examples under high temperature and high pressure.

[0115] As can be seen from Table 1, the coating of Example 1 prepared using the method of the present invention shows significant improvement in all aspects of performance, exhibiting the best effect. Comparative Example 1, without modification, shows the worst performance. Comparative Example 2, deposited using magnetron sputtering, performs poorly, and Comparative Example 3, without densification treatment, shows limited performance improvement.

[0116] Comparative Example 4 To further prepare the three-layer hydrogen embrittlement resistant composite coating material described in Example 2 of this invention, single-layer and two-layer hydrogen embrittlement resistant coating materials were also prepared. The single-layer material was prepared using a plasma-enhanced magnetron sputtering method (specific process conditions are the same as in Example 2) as an Al2O3 coating. The two-layer material (two YSZ-ZrO2 composite coatings and one CrN-Al2O3 composite coating) was prepared using a dual-energy simultaneous deposition method combining laser cladding and high-speed oxygen fuel spraying (HVOF) as described in this invention. The thickness of the two 60%YSZ-40%ZrO2 composite coatings was 60-100 micrometers, and the thickness of the two 55%CrN-45%Al2O3 composite coatings was 70-120 micrometers.

[0117] The obtained coatings were subjected to performance tests under the following conditions: hydrogen pressure: 100 MPa, temperature: 860℃, and exposure time: 500 hours. The results of the tested parameters, including coating porosity, hydrogen permeability reduction rate, thermal shock cycling, adhesion, oxidation depth, pyrolysis density, and interfacial delamination, are shown in Table 2.

[0118] Table 2 Comparison of hydrogen embrittlement resistance test results of different coatings under high temperature and high pressure

[0119] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A high-temperature, high-pressure resistant, hydrogen-embrittlement-resistant composite coating, characterized in that, It includes a hydrogen-capturing layer, a hydrogen-blocking layer, and a barrier layer arranged sequentially; the hydrogen-capturing layer is a composite layer based on rare earth metal elements, alloy matrix elements, and refractory metal elements; the hydrogen-blocking layer is a metal-ceramic composite layer containing a metal matrix and a nano-ceramic reinforcing phase dispersed therein in a gradient; the barrier layer includes a ceramic matrix layer, a nano-reinforcing material layer, and a nano-metal oxide atomic deposition layer arranged sequentially.

2. The high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to claim 1, characterized in that, The components and their mass percentages in the hydrogen-capturing layer include: 0.01-5% rare earth metal elements, 30-75% alloy matrix elements, and 20-65% refractory metal elements.

3. The high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to claim 1, characterized in that, The rare earth metal element is one or more of cerium, lanthanum, ytterbium, neodymium, neodymium, samarium, and neodymium; the alloy matrix element is two or more of nickel, cobalt, iron, and aluminum; and the refractory metal element is one or more of chromium, molybdenum, tungsten, tantalum, niobium, and titanium.

4. The high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to claim 1, characterized in that, In the hydrogen barrier layer, the metal matrix material includes two or more of nickel, cobalt, chromium, iron, molybdenum, tungsten, titanium, aluminum, stainless steel alloy, and nickel-based superalloy; the nano-ceramic reinforcing phase is two or more of nano-metal carbides, nitrides, borides, rare earth oxides, and metal hydrides.

5. The high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to claim 1, characterized in that, The components and their mass percentages in the hydrogen barrier layer include: metal matrix 30-90%; nano-ceramic reinforcing phase 10-70%.

6. The high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to claim 1, characterized in that, From the contact surface with the hydrogen-trapping layer, the content of the nano-ceramic reinforcing phase in the hydrogen barrier layer shows an increasing trend.

7. The high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to claim 1, characterized in that, The ceramic matrix layer in the barrier layer contains three or more of the following materials: yttrium-stabilized zirconium oxide, zirconium oxide, aluminum oxide, chromium oxide, ammonium oxide, silicon carbide, silicon nitride, aluminum nitride, mullite, zirconium diboride, titanium diboride, boron carbide, rare earth oxides, rare earth silicates, and glass ceramics; the nano-reinforcing material is composed of one or more nanomaterials.

8. The high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to claim 1, characterized in that, The components and their mass percentages in the ceramic matrix layer and nano-reinforcing material layer of the barrier layer are as follows: ceramic matrix material 60-99%, nano-reinforcing material 1-40%; the particle size of the nano-reinforcing material is 1-500nm.

9. The high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to claim 1, characterized in that, The total thickness of the high-temperature and high-pressure resistant hydrogen embrittlement-resistant composite coating is 5-200 μm; the thickness of the hydrogen-capturing layer is 1-20 μm; and the thickness of the hydrogen-blocking layer is 2-100 μm.

10. The method for preparing the high-temperature, high-pressure, hydrogen-embrittlement-resistant composite coating according to any one of claims 1 to 9, characterized in that, Includes the following steps: 1) Substrate pretreatment The substrate to be coated with the high-temperature, high-pressure, and hydrogen embrittlement resistant composite coating is subjected to precision grinding, plasma degreasing, ultrasonic cavitation cleaning, and laser texturing in sequence; the surface roughness is controlled to Ra≤3.2μm. 2) Dual-energy simultaneous deposition preparation of hydrogen-trapping layers Using rare earth metal materials, alloy matrix materials and refractory metal materials as the main raw materials, a dual-energy synchronous deposition process combining laser cladding and high-speed oxygen fuel spraying is adopted. The laser and fuel spray gun are moved together on the substrate surface until the required thickness is reached. After cooling, a hydrogen-capturing layer is obtained. 3) Gradient deposition of hydrogen barrier layer Using metal matrix material and nano-ceramic reinforcing phase material as the main raw materials, a bottom coating mainly composed of metal matrix material is first deposited by cold spraying technology. Then, an intermediate equilibrium layer with increasing nano-ceramic reinforcing phase content and an upper coating mainly composed of ceramic material are deposited by plasma-enhanced magnetron sputtering to obtain the hydrogen barrier layer. 4) Preparation of barrier layer by multi-field synergistic deposition Using ceramic matrix precursor materials and nano-reinforcing materials as the main raw materials, suspension plasma spraying and nano-aerosol deposition were carried out sequentially; then, using metal oxide metal-organic precursors as raw materials, atomic layer deposition nano-sealing treatment was carried out to prepare a barrier layer. 5) Densification treatment of multilayer composite materials The composite coating obtained in steps 2) to 4) is further subjected to ultrasonic vacuum isostatic pressing or laser remelting to densify the multilayer composite material, thereby obtaining the high temperature and high pressure resistant and hydrogen embrittlement resistant composite coating.